Ontology after Carnap - Blatti, Stephan 1975-; Lapointe, Sandra (Oxford University Press, 2016)
Rudolf Carnap's deflationary approach to ontology is once again attracting considerable interest and support. 11 original essays by leading voices in metametaphysics deepen our understanding of Carnap's contributions to metaontology, and explore how his legacy can be mined for insights into the contemporary debate
This edition previously issued in print: 2016
Keywords: Carnap, Rudolf / 1891-1970; Carnap, Rudolf -- 1891-1970; Ontology; Ontologie; Aufsatzsammlung